Nesting behaviour and notes on mimetic relationships of Hoplisoides vespoides Smith from Brazil (Hymenoptera: Crabronidae). - Buys, Sandor Christiano (Contributions to Entomology = Beiträge zur Entomologie, 2008)
The nesting behaviour of Hoplisoides vespoides (Smith, 1873) is described based on observations carried out in southeastern Brazil. Notes on mimetic relationships of this species with vespid wasps and with a stratomyid fly are also provided. Umbonia spinosa (Fabricius, 1775) (Hemiptera: Membracidae) is reported as prey.KeywordsWasp, biology, reproduction, mimicry, Umbonia spinosa, Hoplitimyia mutabilis.